PENERAPAN DAN PENDEKATAN BERDASARKAN GAYA ALIRAN DAN TEORI KEPEMIMPINAN - Wasiyem; Amanda Putri Harsana; Della Dwi Syahpira; Zulaila (STKIP Subang, 2024)
Leadership is a vital element in achieving organizational success. A leader not only serves as the main mover, but must also be able to influence, motivate and direct the team to achieve common goals. The method used is literature study, which includes collection, analysis and interpretation of related literature data. The research results show that effective leadership requires style adaptation based on the organizational context, challenges faced, and leader characteristics. This research confirms that leadership is not just an innate talent, but can also be developed through education, experience and consistent training. Successful leaders are those who are able to create synergy within the team, provide inspiration, and ensure that every team member feels involved in achieving organizational goals. In conclusion, organizational success depends greatly on the leader's ability to manage interpersonal relationships, adopt relevant leadership styles, and build a harmonious and productive work environment.